Do you know how much you pay for water? - Monteiro, H.; Roseta-Palma, C.; Rita Martins (International Water Association World Water Congress, 2014)
Water demand management is crucial to achieve a balance between available resources and consumption. Water prices, in particular, are broadly accepted as a way of increasing economic efficiency in use as well as the financial sustainability of utilities and, if they are properly set, even environmental sustainability. Water supply systems should therefore be managed taking into consideration consumer price reactions, and many studies have assessed these through the estimation of water demand functions. Most point to fairly low values of price demand elasticities (range: -0,1 to -0,6). However, a few authors have noted that residential consumers are not always fully informed of their water price and this naturally has an effect of the role prices can play in moderating consumption. In order to improve our understanding of consumer price perceptions a household survey was performed in the summer of 2012, through which we were able to collect detailed information on the characteristics of dwellings, households and respondents, on consumer habits, on tariff, bill and consumption awareness and on attitudes towards environmental and financial sustainability. In this paper we describe the main outcomes of the survey and discuss their implications for utility pricing decisions and for further demand estimation work.